Capital Market Union – Perspectives on Changes in the Financial System Model in the European Union - Janicka, Małgorzata Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Currently the EU is working on the building of the so‑called Capital Markets Union. The undertaken restructuring of the financing model is designed to make a shift in the main channel through which enterprises raise investment funds, from loans to capital, and – as a result – contribute to more dynamic growth in the EU Member States. So far, the key problem with insufficient dynamics of Economic growth in the EU seems to stem not so much from the structure of investment financing but from mechanisms of the euro zone, which economically polarise its members. The European Union should, first and foremost, thoroughly analyse and reformulate the constituting principles of the euro zone, instead of making another attempt to deepen capital markets integration and changing the financing model dominant in the EU Member States. The objective of the paper is to analyse conditions and rationale of the shift in the role which the banking sector plays in transferring investment resources for the benefit of the European Union capital markets (intensification of disintermediation). Conclusions from the analysis were formulated based on qualitative studies and analyses of source materials prepared by the EU, as well as research and financial institutions (surveys, reports, recommendations), and on the basis of available data.